HOSPITAL EMPLOYEES’ PERCEPTION OF MARKETING STRATEGY AT H. ABDUL MANAP GENERAL HOSPITAL IN JAMBI CITY - Milya Timeida; Kurnia Sari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: A hospital is required to be capable of maintaining its existence by developing effective marketing strategies to encounter the globalization challenges. The marketing strategy in the hospital is influential for its activities to provide appropriate services to the patient's needs. This study aims to determine the hospital employees’ perception towards priority marketing strategy at H. Abdul Manap Regional Hospital. Methods: This study was used the quantitative method with the descriptive analytic research. This research conducted in 602 people while the samples were 240 people, selected by accidental sampling technique. The primary data collection was conducted by employing a questionnaire as the survey method. The data analysis carried out was univariate analysis to obtain a percentage value description for each marketing strategy. Results: The results identified that price was the top priority marketing strategy voted by 171 respondents (71.3%). On the second rank, Product was voted as the top marketing strategy by 141 people (58.8%). In the third position, Professionalism was voted by 132 people (55.0%) as the top priority for marketing strategy. Conclusions: The research concludes that the hospital employees perceived that H. Abdul Manap General Hospital needed to prioritize price, product, and professionalism in developing its marketing strategies. It is advised that H. Abdul Manap General Hospital revise its price, develop new products based on patient needs, and provide professional human resources with good communication skills.